2012
DOI: 10.1002/dvg.20803
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin–proteasome system components are upregulated during intestinal regeneration

Abstract: The ubiquitin proteasome system (UPS) is the main proteolytic system of cells. Recent evidence suggests that the UPS plays a regulatory role in regeneration processes. Here we explore the possibility that the UPS is involved during intestinal regeneration of the sea cucumber Holothuria glaberrima. These organisms can regenerate most of their digestive tract following a process of evisceration. Initially, we identified components of H. glaberrima UPS, including sequences for Rpn10, β3 and ubiquitin-RPL40. Predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…Our previous studies suggested that the proteasome could be playing an important role during intestinal regeneration in H. glaberrima (Pasten et al, 2012). Therefore, our first step was to determine if proteosomal enzymatic activity was present in extracts of regenerating intestine.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous studies suggested that the proteasome could be playing an important role during intestinal regeneration in H. glaberrima (Pasten et al, 2012). Therefore, our first step was to determine if proteosomal enzymatic activity was present in extracts of regenerating intestine.…”
Section: Resultsmentioning
confidence: 99%
“…We had recently characterized proteasome components from H. glaberrima and shown them to be overexpressed during intestinal regeneration (Pasten et al, 2012). Thus our hypothesis was that, similar to what occurs in other systems (Glickman and Ciechanover, 2002), proteasomes could modulate different biological processes during intestinal regeneration, such as cell division or apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In echinoderms, Patruno et al () demonstrated that levels of conjugated ubiquitin increased during the early post‐amputation phase and later growth during arm regeneration in the brittle star Amphiura filiformis , reflected in highly expressed transcripts for components of the protein degradation system (polyubiquitin and proteasome subunits) and structural proteins, such as actin and collagen (Burns et al ). Pasten et al () determined the expression levels of Rpn10, b3, and Ub‐RPL40 during early intestinal regeneration (3, 7, and 14 d) and compared them with those of normal intestines using gene expression microarrays in the sea cucumber, Holothuria glaberrima . Rpn10, β3, and Ub‐RPL40 genes were expressed at all stages of regeneration and in normal animals, but expression levels were significantly higher during the very early stages of intestinal regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Recently high throughput gene expression techniques have been applied to echinoderm regeneration significantly increasing the number of candidate genes and timescales involved in this process. Gene expression profiling of regenerating ophiuroid arms and holothurians intestine revealed that some of the differentially expressed genes are homologs of genes known to be involved in regenerationrelated processes such as wound healing, cell proliferation, differentiation, morphological plasticity, cell survival, stress response, pathogenic challenge, and neoplastic transformation [126,[133][134][135][136][137][138][139].…”
Section: Echinodermsmentioning
confidence: 99%